„War within a war”. The role of the two autonomous entities of Western Bosnia in the Bosnian conflict (1993–1995) - Wybranowski, Dariusz (Balcanica Posnaniensia. Acta et studia, 2025)
The article presents the circumstances surrounding the creation and collapse of the autonomous Provinces of Western Bosnia (1993–1994) and the Republic of Western Bosnia (1994–1995) in the context of events related to the war in Croatia and Bosnia and Herzegovina in 1992–1995. Based on multilingual literature on the subject, the article describes military operations in the Cazin Krajina region, the manner in which leader Fikret Abdić exercised power, and his fate after the collapse of the two „autonomies”. These small quasi-states had their own political institutions and armies. F. Abdić was considered a critic and political rival of the President of BiH Alija Izetbegović. He declared that his goal was political cooperation with Serbs and Croats on the basis of common economic interests. His secession from BiH was treated in Sarajevo as political „treason”. With the end of the Bosnian-Croatian fighting, F. Abdić lost the ability to manoeuvre between the parties of the conflict. Moreover, he was not a partner for Western countries. They recognised only his political rival, Alija Izetbegović, as the legitimate representative of all Bosnian Muslims. The elimination of F. Abdić's „autonomy” was seen as a natural consequence of the end of the Bosnian conflict.